The Urgency of Maritime Policy to Welcome a Golden Indonesia 2045 - Prakoso, Lukman Yudho; Alman, Fariel Zulfikar; Rianto, Rianto (PT FORMOSA CENDEKIA GLOBAL, 2024)
The dynamics of the global strategic environment have an impact on world threats in the future. Indonesia has set a vision until 2045. How urgent matters must be prepared within the best policy framework to achieve the desired goals. This research uses Lukman Yudho Prakoso's policy implementation theory and qualitative descriptive methods. The research results show that there are still many things related to urgent policies that are carried out in an integrative, interactive, transparent, controlled and accountable manner; The results of the research show that several strategies are needed so that maritime policies are implemented effectively and efficiently in achieving the vision of a golden Indonesia 2045. As a recommendation, strategic steps are needed such as improving maritime infrastructure, strengthening maritime security, sustainable management of marine resources, developing the maritime economy. , strengthening human resources, increasing transparency and accountability, as well as cross-sector collaboration to achieve these goals.